2015
DOI: 10.1155/2015/512675
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Oligosaccharides and Their Esters from Traditional Chinese Medicines: Chemical Structures and Biological Activities

Abstract: A great number of naturally occurring oligosaccharides and oligosaccharide esters have been isolated from traditional Chinese medicinal plants, which are used widely in Asia and show prominent curative effects in the prevention and treatment of kinds of diseases. Numerous in vitro and in vivo experiments have revealed that oligosaccharides and their esters exhibited various activities, including antioxidant, antidepressant, cytotoxic, antineoplastic, anti-inflammatory, neuroprotective, cerebral protective, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 99 publications
0
26
0
Order By: Relevance
“…Scrophularia ningpoensis (Family Scrophulariaceae), commonly known as Ningpo figwort or Chinese figwort, is used since centuries as an ingredient of Chinese herbal tea for its antipyretic, anti‐inflammatory, antioxidant, anti‐angiogenic, neuroprotective, antidepressant, cardiovascular‐protective, antidiabetic, immunostimulating, memory enhancing and antineoplastic properties. The main active chemical constituents identified to be responsible for these properties include angoroside C, acetoside, sibirioside A, 6‐O‐caffeoyl sucrose and oligosaccharides of raffinose, stachyose and verbascose . Although it was recently reported by a study that harpagoside, a chemical constituent of S. ningpoensis , along with other Chinese herbs ( P. notoginseng , S. miltiorrhiza and A. membranaceus ) is responsible for the antidiabetic retinopathy potential of clinically established Chinese capsules Fufang Xueshuantong, certain other constituents of S. ningpoensis also posses this potential.…”
Section: Chinese Herbs As Potential Antidiabetic Retinopathy Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Scrophularia ningpoensis (Family Scrophulariaceae), commonly known as Ningpo figwort or Chinese figwort, is used since centuries as an ingredient of Chinese herbal tea for its antipyretic, anti‐inflammatory, antioxidant, anti‐angiogenic, neuroprotective, antidepressant, cardiovascular‐protective, antidiabetic, immunostimulating, memory enhancing and antineoplastic properties. The main active chemical constituents identified to be responsible for these properties include angoroside C, acetoside, sibirioside A, 6‐O‐caffeoyl sucrose and oligosaccharides of raffinose, stachyose and verbascose . Although it was recently reported by a study that harpagoside, a chemical constituent of S. ningpoensis , along with other Chinese herbs ( P. notoginseng , S. miltiorrhiza and A. membranaceus ) is responsible for the antidiabetic retinopathy potential of clinically established Chinese capsules Fufang Xueshuantong, certain other constituents of S. ningpoensis also posses this potential.…”
Section: Chinese Herbs As Potential Antidiabetic Retinopathy Therapymentioning
confidence: 99%
“…The main active chemical constituents identified to be responsible for these properties include angoroside C, acetoside, sibirioside A, 6-O-caffeoyl sucrose and oligosaccharides of raffinose, stachyose and verbascose. [66,67] Although it was recently reported by a study that harpagoside, a chemical constituent of S. ningpoensis, along with other Chinese herbs (P. notoginseng, S. miltiorrhiza and A. membranaceus) is responsible for the antidiabetic retinopathy potential of clinically established Chinese capsules Fufang Xueshuantong, [68] certain other constituents of S. ningpoensis also posses this potential. Acetoside is an aldose reductase inhibitor [69] and thus is liable to elicit similar beneficial effects as astragaloside IV (already discussed above) and helps in attenuating the pathological occurrences during diabetic retinopathy.…”
Section: Scrophularia Ningpoensismentioning
confidence: 99%
“…Oligosaccharides are naturally occurring compounds widely distributed in the roots, barks, leaves, or whole parts of plants. Numerous lines of evidence have revealed that oligosaccharides possess many biological activities, such as antioxidant, antiinflammatory, antimicrobial, prebiotic, and antidiabetic activities (Chen et al, ; Sousa et al, ; Vogt et al, ). Notably, previous studies in our lab suggested that some oligosaccharides may provide a prospective source for antidepressants discovery (Zhang et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…5-Azacytidine (5-aza) is often used to induce differentiation of MSCs into myocardial cells; however, 5-aza is associated with various adverse effects as an antitumor drug (Borodovsky et al, 2013). A number of studies focusing on traditional Chinese medicine extracts found that Rehmannia glutinosa oligosaccharide (RGO), extracted from R. glutinosa, could promote the differentiation of MSCs into skeletal muscle myoblasts in vitro (Chen et al, 2015). In addition, RGO has also been shown to regulate immunity, protect the myocardium, as well as exert antidiabetic and antitumor effects (Lai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%